2017
DOI: 10.1177/1066896917712453
|View full text |Cite
|
Sign up to set email alerts
|

Syringoid Eccrine Carcinoma of the Foot: Report of a Rare Cutaneous Adnexal Neoplasm

Abstract: Syringoid eccrine carcinoma is a rare malignant adnexal tumor that typically presents in the head and neck region. Involvement of the extremities is uncommon, with only a few cases reported in the literature. Here, we report our experience with a rare case of syringoid eccrine carcinoma occurring on the plantar surface of the right foot in a 47-year-old African American woman. Histologically, incisional biopsy revealed a tumor consisting of tubulocystic structures lined by basaloid cells with an infiltrative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…In the differential diagnosis with ADC, perineural infiltration and histological presentation might resemble ADC with a cribriform morphological pattern; however, the positivity for CEA and S100 in our patient would be more consistent with the tubular pattern [21]. Thus, in addition to the immunohistochemical pattern disagreeing with the morphological pattern, there is no accumulation of mucin, as occurs in ADC, favoring the diagnosis of SEC [3,14,19,17]. Imaging studies have been reported to be important but for delimiting the lesion, but not for diagnosis of SEC [11], or searching for metastases [9,10,15].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the differential diagnosis with ADC, perineural infiltration and histological presentation might resemble ADC with a cribriform morphological pattern; however, the positivity for CEA and S100 in our patient would be more consistent with the tubular pattern [21]. Thus, in addition to the immunohistochemical pattern disagreeing with the morphological pattern, there is no accumulation of mucin, as occurs in ADC, favoring the diagnosis of SEC [3,14,19,17]. Imaging studies have been reported to be important but for delimiting the lesion, but not for diagnosis of SEC [11], or searching for metastases [9,10,15].…”
Section: Discussionmentioning
confidence: 67%
“…Tumor cells can organize into nests, cords, or tubules, some of which exhibit a morphology resembling tadpole-like syringoma due to the cords of epithelial tissue. Cytonuclear atypia is not very evident, as is the presence of mitotic activity, which may even be absent [1,11,14,16]. The epithelial component of the tumor may show a cribriform pattern in focus (Figure 3), which makes it difficult to distinguish from other tumors [3].…”
Section: Discussionmentioning
confidence: 99%
“…O carcinoma écrino (CE) é um neoplasma maligno raro das glândulas sudoríparas que pode acometer cães, gatos [7] e humanos. Em pessoas o CE tem maior frequência em cabeça e pescoço, podendo ocorrer metástase para qualquer parte do corpo [10] e, geralmente, se manifesta a partir da meia idade [2].…”
Section: Introductionunclassified
“…Em ambos os casos, os fragmentos excisados foram acondicionados em solução de formalina tamponada a 10% e processados rotineiramente, incluídos em parafina, cortados a 4 µm, corados com hematoxilina (Hematoxilina de Harris) 1 e eosina (Eosina Amarelada -Ci45380) 2 , seguidos de avaliação histopatológica.…”
Section: Introductionunclassified